Toxicological studies and assessment of pharmacological activities of Abrus precatorius L. (Fabaceae) ethanolic leaves extract in the management of pain, psychiatric and neurological conditions: An in-vivo study - Sumanta Mondal, Debjit Ghosh, Krishna Chaitanya Anusuri, Seru Ganapaty (Journal of Applied Pharmaceutical Science, 2017)
Abrus precatorius L. is an important medicinal plant belonging to family Fabaceae. The present study was conducted to perform pre-clinical safety evaluation and study the pharmacological effects of the ethanolic leaves extract of A. precatorius in management of pain, psychiatric and neurological conditions. Acute toxicity was performed to study the general behavioural pattern of mice after treatment with the test extract (single doses of 100, 1000, 1500 mg/kg, body weight) and sub-acute toxicity studies were performed to study the toxic effects of the test extract (500 mg/kg, per os for 14 days) on different biochemical and haematological parameters, body and organ weight and histopathology of liver and kidney. The toxicological evaluation of A. precatorius ethanolic leaves extract revealed that it has a reasonable safety profile. Analgesic and neuropharmacological effects like muscle relaxant, locomotor, anti-epileptic and anti-depressant activities were also studied on different animal models. The result showed that ethanolic leaves extract of A. precatorius at the doses of 300 and 500 mg/kg, p.o. possesses significant analgesic and neuropharmacological activities. Thus the present study shows that A. precatorius possesses a reasonable safety profile and can be used in the management of pain, psychiatric and neurological conditions.
Keywords: Abrus precatorius, Analgesic, Diazepam, Neurological disorders, Toxicity.